Pertanggungjawaban Perusahaan Pengangkut pada Tindakan General Average terhadap Kerugian Kargo yang Diangkut - Lova, Sandra A. M.; Chumaida, Zahry Vandawati (Jurnal Hukum & Pembangunan, 2026)
Maritime transportation plays a vital role in supporting trade, yet risks such as perils of the sea or ship accidents caused by unseaworthiness often lead to disputes, particularly when General Average is declared. This practice, recognized since Roman times, has evolved into a legal concept in marine insurance to distribute deliberate sacrifices made for the safety of the vessel and its cargo. This study aims to analyze the liability of carriers in General Average actions and to evaluate the concept as a fair mechanism for loss distribution. The research employs a normative juridical method with statutory, conceptual, and comparative approaches, using data obtained through library research of legislation, maritime law literature, insurance policies, and relevant court decisions. Findings reveal that General Average originates from the York-Antwerp Rules as a form of international legal unification, compared with the Indonesian Commercial Code (KUHD) on avariij umum. The conclusion highlights that while General Average is recognized as a mechanism of shared responsibility, agreements in carriage contracts and cargo insurance policies are essential to determine the scope of liability and ensure proportional allocation of losses.